Meningkatkan Kemampuan Mengenal Bangun Datar Menggunakan Media Geometri Digital Bagi Murid Disabilitas Intelektual - Yolanda, Mutiara; Efrina, Elsa; Marlina, Marlina; Yuliana, Syari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Geometry learning for students with intellectual disabilities requires media that can present the concept of plane figures in a concrete and engaging way due to their limitations in understanding abstract material. One alternative that can be used is digital geometry media that combines visual and interactive elements to support the learning process. This study aims to determine the effectiveness of digital geometry media in improving the ability to recognize plane figures in students with intellectual disabilities. The study used an experimental method with a Single Subject Research (SSR) type A-B design. The subject of the study was a ninth-grade student with intellectual disabilities at the Bima Padang Special Needs School for Autism who had not been able to recognize plane figures. Data were collected using a checklist test and analyzed through visual analysis within and between conditions. The results showed that the student's ability score increased from 35.7% in the baseline phase to 92.8% at the end of the intervention phase. The analysis also showed a level change of 42.8% with an overlap percentage between conditions of 0%. These findings indicate that digital geometry media is effective in improving the ability to recognize plane figures in students with intellectual disabilities.